Nutritional Characterisation of European Aquaculture Processing By-Products to Facilitate Strategic Utilisation - Malcorps, Wesley; Newton, Richard W.; Sprague, Matthew; Glencross, Brett D.; Little, David C. (Frontiers in Sustainable Food Systems, 2021)
Sustainability analyses of aquaculture typically ignore the fate and value of processing by-products. The aim of this study was to characterise the nutritional content of the common processing by-products (heads, frames, trimmings, skin and viscera) of five important finfish species farmed in Europe; Atlantic salmon (Salmo salar), European seabass (Dicentrarchus labrax), gilthead seabream (Sparus aurata), common carp (Cyprinus carpio) and turbot (Psetta maxima) to inform on best utilisation strategies. Our results indicate a substantially higher total flesh yield (64–77 %) can be achieved if fully processed, compared to fillet only (30–56 %). We found that heads, frames, trimmings and skin from Atlantic salmon, European seabass, gilthead seabream and turbot frames showed medium to high edible yields, medium to high lipid, and medium to high eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) content, indicating significant potential for direct use in human food. By-products which are unattractive for use in food directly but have low ash content and medium to high crude protein, lipid and EPA and DHA content, such as viscera, could be directed to animal feed. Skin showed interesting nutritional values, but has more potential in non-food applications, such as the fashion, cosmetic and pharmaceutical industries. The results indicate potential to increase the direct food, animal feed and non-food value of European aquaculture, without an increase in production volumes or the use of additional resources. The importance of changing consumer perceptions and addressing infrastructure and legislative barriers to maximize utilisation is emphasised.